Mechanisms of organelle division and inheritance and their implications regarding the origin of eukaryotic cells - KUROIWA, Tsuneyoshi (The Japan Academy, 2010)
Mitochondria and plastids have their own DNAs and are regarded as descendants of endosymbiotic prokaryotes. Organellar DNAs are not naked in vivo but are associated with basic proteins to form DNA-protein complexes (called organelle nuclei). The concept of organelle nuclei provides a new approach to explain the origin, division, and inheritance of organelles. Organelles divide using organelle division rings (machineries) after organelle-nuclear division. Organelle division machineries are a chimera of the FtsZ (filamentous temperature sensitive Z) ring of bacterial origin and the eukaryotic mechanochemical dynamin ring. Thus, organelle division machineries contain a key to solve the origin of organelles (eukaryotes). The maternal inheritance of organelles developed during sexual reproduction and it is also probably intimately related to the origin of organelles. The aims of this review are to describe the strategies used to reveal the dynamics of organelle division machineries, and the significance of the division machineries and maternal inheritance in the origin and evolution of eukaryotes.